Oxytocin Response Following Playful Mother–Child Interaction in Survivors of the Great East Japan Earthquake - Nawa, Nobutoshi; Nakamura, Kazuaki; Fujiwara, Takeo (Frontiers in Psychiatry, 2020)
Background: Children who are exposed to natural disasters are at greater risk of developing mental and behavior problems. Prior studies have suggested that positive parenting practices could prevent child mental and behavior problems among those who were exposed to natural disasters. Parent-child interaction increases oxytocin level in parents and infants; however, studies assessing the change in oxytocin level after positive parent-child interaction and its effect on child behavior problems among preadolescents who were exposed to natural disasters are lacking. This study investigated whether playful interaction stimulated oxytocin levels in 34 mother-child dyads who experienced the 2011 Great East Japan Earthquake in Kesennuma City in Miyagi Prefecture, Japan, and the effect of the maternal oxytocin changes on child behavior problems. Methods: Participants were recruited in 2012 after the Great East Japan Earthquake. Annual surveys were conducted from 2012 to 2017. Salivary oxytocin level was assessed before and after the playful interaction in 2015. Behavior problems were evaluated by caregivers, using the Child Behavior Checklist (CBCL) in 2017. Fixed effect regression analyses were conducted to determine the effect of playful mother-child interaction on oxytocin level by comparing the change in the 10 minutes after the interaction with the change in the 10 minutes before the interaction. We also examined the effect of maternal oxytocin changes before and after the playful interaction on the onset of child behavior problems in 2017. Results: A significant increase in maternal oxytocin level was detected following playful interaction, especially among mothers of first-born boys (2.63 pg/mg protein. 95% CI: 0.45, 4.81). Maternal psychological distress and trauma were also negatively associated with an increase of oxytocin levels. The increase in maternal oxytocin level was significantly associated with lower externalizing problem score of children two years later. Conclusion: Our results might suggest a rational for potential preventive intervention for child behavior problems through playful mother-child interaction after natural disasters.